Effectiveness, safety and tolerability of Ozenoxacin 2% lotion vs Clindamycin 1% lotion in mild to moderate truncal acne: An open label randomized controlled clinical trial - Anupam Das; Sambit Chatterjee; Saikat Banerjee; Sujata Sengupta (Clinical and Experimental Dermatology, 2026)
Abstract Background Truncal acne is a frequently encountered but relatively understudied manifestation of acne vulgaris and is often associated with significant physical discomfort and psychosocial impact. Topical clindamycin has been extensively used in mild to moderate acne, however, there are concerns regarding antimicrobial resistance which has prompted interest in alternative topical agents. Ozenoxacin, a non-fluorinated quinolone, offers broad-spectrum antibacterial activity with minimal systemic absorption. Objectives To compare the effectiveness, safety, and tolerability of ozenoxacin 2% lotion with clindamycin 1% lotion in patients with mild to moderate truncal acne. Methods This institution-based, open-label, randomized controlled trial included 78 patients aged 18–35 years with mild to moderate truncal acne. Participants were randomized to receive either ozenoxacin 2% lotion or clindamycin 1% lotion applied twice daily for 12 weeks. Both groups received adapalene 0.1% gel once daily at bedtime. Clinical efficacy was assessed using Investigator Global Assessment (IGA), total lesion count, inflammatory and non-inflammatory lesion counts, Cardiff Acne Disability Index (CADI), and Dermatology Life Quality Index (DLQI). Safety was evaluated through adverse event monitoring. Results Thirty-five patients in the ozenoxacin group and thirty-four in the clindamycin group completed the study. Both groups demonstrated statistically significant improvement from baseline in all efficacy parameters at 12 weeks (p < 0.05). Intergroup comparisons showed no statistically significant differences across clinical or quality-of-life outcomes. Both treatments were well tolerated, with only mild and transient adverse effects reported. Conclusion Ozenoxacin demonstrated comparable efficacy and tolerability to clindamycin when used in combination with adapalene, in truncal acne.